Correlation between Ubiquinone Levels, Lactate Dehydrogenase, and Lactate on Acute Myocardial Infarction - Purwanto Adhipireno; Lisyani Budipradigda Suromo; Charles Limantoro; Andreas Arie Setiawan; Jessica Christanti; Dwi Retnoningrum; Nyoman Suci Widiastiti; Ariosta Ariosta (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Ubiquinone is an antioxidant that plays a role in preventing endothelial damage, thereby reducing the risk of myocardial infarction. In myocardial infarction, there is a decrease in ubiquinone levels and energy production in the form of ATP. Both stimulate anaerobic metabolism, which increases lactate dehydrogenase and lactate levels. This study aimed to analyze the correlation between ubiquinone levels, lactate dehydrogenase levels, and lactate levels in patients with acute myocardial infarction. This study was an analytical observational study with a cross-sectional approach. The normality of data was analyzed using the Kolmogorov-Smirnov test, and the correlation among variables was analyzed using the Spearman Rank test. The number of research subjects was 52, consisting of 25 research subjects with STEMI and 27 with NSTEMI. The median of ubiquinone, LDH, and lactate levels was 12.52 ng/mL (5.6–412.2); 310 U/L (3-1212); and 4 mmol/L (0.8 – 22), respectively. The correlation test results between ubiquinone levels with LDH levels obtained p=0.4 with r=-0.35; correlation test results between LDH levels and lactate levels obtained p=0.09, with r = -0.14. There was no correlation between acute myocardial infarct patients' ubiquinone levels, LDH levels, and lactate levels in AMI patients.